Pemanfaatan Kestrak Daun Mahkota Dewa (Phaleria macrocarpa) sebagai Insektisida Nabati Nyamuk Anopheles - Nurbaiti Nurbaiti; Yamtana Yamtana; Sarjito Eko Windarso (Poltekkes Kemenkes Yogyakarta, 2015)
One of arthopodborne diseases that can be dangerous and even can cause death in human isMalaria, which is transmitted through the bite of Anopheles. Mahkota Dewa (Phaleria macrocarpa) is one of plants that produce saponin, alcoloid and flavonoids which can be used as botanical insecticide. The purpose of this study was to utilize the leaf extract of the plant as insecticide for Anopheles by conducting a true experiment with post test only with control group design and took place at The Vector Laboratory of Environmental Health Department of Yogyakarta Polytechnic of Health. The mosquitoes aged 2-4 days tested in the experiment were reared by the researcher and there were three extract concentrations used to spray the insects, i.e. 30 %, 40% and 50 %. Confounding variables which were controlled are age and feeds of the mosquitoes,temperature and the atomizer. The death of the insects was calculated by using Abbott formula.Data which were analyzed by One Way Anova test at 0,05 level of significance obtained a pvalue less than 0,001 which can be interpreted that various concentrations of Mahkota Dewa leaf extraction give different effects on Anopheles mortality. Based on the subsequent LSD test, it was found that the most effective concentration is 50 %.